TI_GERICHTE 72.2016.4 vom 15. November 2018 , Lesioni gravi, sub. semplici, per un pugno al volto, frattura osso - TI Tribunale d'appello (2018)
Lesioni gravi, sub. semplici, per un pugno al volto, frattura osso